Genre connections : lessons to launch literary and nonfiction texts - McGregor, Tanny (Portsmouth, NH : Heinemann, 2013)
McGregor presents a collection of ideas about how to launch genres, how to introduce your students to the personalities of each, and how to build a curiosity and appreciation for what each genre has to offer. Her lessons use everyday objects, works of art, music, and anchor charts to help readers get acquainted with seven commonly taught genres and to discover what makes them unique.
Prologue: My first book -- A very good place to start -- Poetry: a match made in heaven -- Adventure and fantasy: beyond realistic fiction -- Historical fiction: the best of both worlds -- Drama: a tough act to follow -- Image reading: stop, look, and learn -- Biography, autobiography, and memoir: such is life -- Informational text: the need to know -- Epilogue: Only one bean.
Includes bibliographical references (pages 111-115) and index.
Keywords: Literary form -- Study and teaching; Youth -- Books and reading; Reading comprehension